(3aVd Cgd GdchaI haVd CgdgGs - (3CHh YHO Gddg eMeO Hf Ydj Hf GdMSf Hf YHO GdQMef GdYdhj GdMSjfjs ((3YeQ Hf CMeO s)
(3ChdgG (B:s
(3CNHQfG GdTQja CHh YHO Gddg eMeO Hf Ydi bGd QShd Gddg Udi Gddg Ydjg hSde dCHf eSYhO deG CSQi Hi Edi GdSeGA GdOfjG CQGfi LHQjd eSLO s
(3BNQgG (B:s
(3Yf YHO Gddg Hf eMeO Hf GdMfajI bGd GdchaI MQe fhM hMQe ghO hgj MQefG ai BNQ GdReGf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs